Applied Academics Applied Mathematics : Frank S. Budnick - Budnick, Frank S. (New York : McGraw-Hill, 1988)
This publication contains the Applied Mathematics Curriculum (Drafting) for grades 11 and 12 for the Cincinnati (Ohio) Public Schools. The curriculum is part of a larger program (the Applied Academics Program), which emphasizes the integration of mathematics and the language arts with vocational content. Included in the document is a description of the Applied Academics Program (including its philosophy, goals, and evaluation policy), the Applied Mathematics Program--Junior Year (including its philosophy, goals, and objectives), the Applied Mathematics Program--Senior Year (including its philosophy, goals and objectives). The curriculum outlines include vocational student objectives and student activities and related academic student objectives and student activities. The appendices contain evaluation instruments and forms. (RH)
Practitioners.
Teachers.
Microfiche.
Keywords: Busniess Mathematics; Ohio (Cincinnati); Guides, Classroom -- Teacher; Reports, Descriptive